2001
DOI: 10.1054/bjoc.2000.1652
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation and forced expression of EWS-Fli1 fusion gene results in changes in the expression of G1regulatory genes

Abstract: Chromosomal translocation t(11;22)(q24:q12) is detected in approximately 90% of tumours of the Ewing family (ET). This translocation results in EWS-Fli1 gene fusion which produces a EWS-Fli1 fusion protein acting as an aberrant transcriptional activator. We previously reported that the inhibition of EWS-Fli1 expression caused the G 0 /G 1 arrest of ET cells. We, therefore, hypothesized that EWS-Fli1 may affect the expression of G 1 regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
93
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 26 publications
9
93
0
1
Order By: Relevance
“…As also expected from previous studies (27), Dox treatment resulted in an Ϸ2-fold decrease in cyclin D1a mRNA levels specifically in A673-shEF1 cells but not in A673-Ctrl cells (Fig. 1B).…”
Section: Ews and Ews-fli1 Affect The Expression Of Cyclin D1 Isoformssupporting
confidence: 91%
“…As also expected from previous studies (27), Dox treatment resulted in an Ϸ2-fold decrease in cyclin D1a mRNA levels specifically in A673-shEF1 cells but not in A673-Ctrl cells (Fig. 1B).…”
Section: Ews and Ews-fli1 Affect The Expression Of Cyclin D1 Isoformssupporting
confidence: 91%
“…Thus, it appears that, in ES cells, downregulation of EWS/FLI-1 expression may be an important contributor to the observed G 1 cell cycle arrest. This interpretation is in agreement with the previous observation that inhibition of the expression of the fusion protein with specific antisense oligodeoxynucleotides induced G 1 cell cycle arrest (Matsumoto et al, 2001). This does not exclude the possibility that abnormalities in G 1 checkpoint regulators known to occur in ES cells (Deneen and Denny, 2001) may also contribute to, and most likely increase their sensitivity to rapamycin.…”
supporting
confidence: 93%
“…; (*), Pp0.02 for test group versus untreated control group Downregulation of EWS/FLI-1 by rapamycin S Mateo-Lozano et al Several studies reported that the induction of cell cycle arrest by rapamycin resulted from a decrease in the levels of cyclins (Seufferlein and Rozengurt, 1996;Decker et al, 2003). Moreover, it has been recently proposed that cyclin-dependent kinase inhibitors and other G 1 regulators are targets of the EWS/FLI-1 transcriptional activity (Matsumoto et al, 2001;Nakatani et al, 2003). Thus, it appears that, in ES cells, downregulation of EWS/FLI-1 expression may be an important contributor to the observed G 1 cell cycle arrest.…”
mentioning
confidence: 99%
“…EWS/Fli-1 is a strong transactivator of the c-myc promoter (Bailly et al, 1994). Several genes such as EAT-2 (Thompson et al, 1996), stromelysin , and fringe (May et al, 1997) are reported to be upregulated, while TGF-b type II receptor (TGFbIIR) (Im et al, 2000), p21 (Matsumoto et al, 2001), and p57KIP2 (Dauphinot et al, 2001) are downregulated. Furthermore, EWS/Fli-1 interacts with hsRPB7, a subunit of human RNA polymerase II (Petermann et al, 1998), and the EWS/ Fli-1 fusion protein alters the IGF-IR signaling pathway (Toretsky et al, 1997).…”
Section: Introductionmentioning
confidence: 99%